Pengaruh Gaya Hidup dan Aksesibilitas Terhadap Keputusan Pembelian Menggunakan Shopee Paylater: Studi pada Perilaku Keuangan Remaja Usia 17-25 Tahun (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of lifestyle and accessibility on purchasing decisions using the Shopee PayLater feature among adolescents aged 17–25. Employing a quantitative approach and multiple linear regression analysis on 73 respondents, the results show that both lifestyle and accessibility have a positive and significant effect on purchasing decisions, both simultaneously and partially. The coefficient of determination (R²) of 79.3% indicates that these variables explain most of the variation in purchasing decisions. A consumptive lifestyle and ease of access are proven to drive adolescent purchasing behavior through digital credit services.